Oil refinery and water pollution in the context of sustainable development: Developing and developed countries. (15th June 2021) - Radelyuk, Ivan; Tussupova, Kamshat; Klemeš, Jiří Jaromír; Persson, Kenneth M.
Abstract: This paper is an attempt to evaluate the impact of the oil refinery industry on water resources worldwide from the point of view of sustainable development (SD). The local laws, reports from the industry and environmental agencies, conditions of the final disposal system were analysed. Key aspects, such as existing approaches for treatment systems, quality of treated wastewater, and ways to assure the safety of them were compared. The comparison between industrialised (represented by the USA and EU) and developing countries (Kazakhstan used as an example) shows that several obstacles, such as loopholes in legislation, historical contamination, and miscommunicating between stakeholders, exist, despite the formal promotion of the SD concept. That policy should be implemented based on the relevant scientific investigation through the possibility of integrating the respective technological development, an adequate system of environmental impact assessment, and fair operational monitoring. Highlights: Oil refineries still discharge contaminated wastewater into water bodies worldwide. Principles of Sustainable water use for the oil refinery sector are defined. An adequate policy regulation makes Sustainable water use in the industry achievable. The policy should implement the Circular Economy, a fair Environmental Impact Assessment, and the transparent environmental monitoring.